Development Of A Moodle-Based Modular Learning System For Network Infrastructure Administration Subjects In Class Xi Competence In Computer And Network Engineering Expertise - Arie Sumartini; Herry Sujaini Herry Sujaini; Urai Salam Urai Salam (Journal Of Social Science (JoSS), 2023)
This research aims to design, determine the profile and effectiveness of the development of a Moodle-based Modular Learning System for network infrastructure administration subjects in class xi computer and network engineering competencies. To achieve the research objectives, the Research and Development (R&D) method is used with the ADDIE development model. With the ADDIE development model, the research is carried out through the stages of (1) Analyze, (2) Design, (3) Develop, (4) Implement and (5) Evaluate. This research was conducted at SMK Negeri 1 Ketapang in the Computer and Network Engineering expertise program class XI with 72 participants. The developed Moodle-based Modular Learning System was validated by 9 design experts with an average recapitulation result of 4.50.